The Normative Circle - Ferraris, Maurizio (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
Where does normativity come from? The intentionalist hypothesis, adopted by the defenders of collective intentionality, implicitly assumes – without either wanting or knowing it – a hypothesis that I call “Pentecostal”, for it comes from heaven. The documentary hypothesis, which I defend in this article, proposes a circle instead: normativity emerges from our animal past, it is fixed in rites and documents, and it shapes our behaviour by generating, in its own turn, other documents. Parole-chiave: Documentality; Intentionality; Pentecost; Emergence; Normativity Indice: Alla prova dei fatti – Il detto di Anassimandro – L’animale capace di promettere – Il denaro prima dell’Anima – Bionde bestie in bolletta – Dalla borsa al valore – Due facce della stessa moneta – “Tu devi!” – Dalla mimesi alla metessi – Rispondere a e rispondere di – Documenti che generano intenzioni che si fissano in altri documenti – Riferimenti bibliografici